2015
DOI: 10.1016/j.ijsu.2015.07.699
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative study of clinical and functional outcomes between anatomic double bundle and single bundle hamstring grafts for arthroscopic anterior cruciate ligament reconstruction

Abstract: We suggest that functional outcome and clinical stability may be better with anatomical double bundle anterior cruciate ligament reconstruction as compared to anatomical single bundle anterior cruciate ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…Sufficient biomechanical strength and better clinical results concerning these grafts have been reported. 3,8,48,54,68,92,96 In addition, the quadriceps autograft is another choice of autograft. 3,36 It has been reported that the quadriceps autograft has the same level of strength with similarly good clinical results and without severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient biomechanical strength and better clinical results concerning these grafts have been reported. 3,8,48,54,68,92,96 In addition, the quadriceps autograft is another choice of autograft. 3,36 It has been reported that the quadriceps autograft has the same level of strength with similarly good clinical results and without severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic techniques have been successfully applied in many clinical disciplines ( 43 , 44 ). In terms of joint surgery, arthroscopy has been widely used in the shoulder, elbow, wrist, hip, knee, ankle and other joints ( 45 50 ), especially in applications in the knee joint, and the technology has progressed ( 51 57 ). As a result, arthroscopic techniques were selected to develop the present model, due a series of advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Although revision ACL reconstruction is promising, the outcome is generally inferior to that of successful primary ACL reconstruction (9,26). Despite double-bundle ACL reconstruction producing superior clinical outcomes to those of single-bundle ACL reconstruction (16)(17)(18)(19)(20)(21)(22)(23)(24), the double-bundle technique has rarely been used in revision ACL reconstruction due to it being technically more challenging (27). Tunnel placement errors, particularly femoral tunnel misplacement, are the most common causes for primary graft failure (28).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with single-bundle ACL reconstruction, the double-bundle technique produced better Lachman and pivot-shift test results, KT arthrometry results and Tegner score after 3-12 years post operation (19). In most cases, double-bundle ACL reconstruction yielded significantly favorable results on KT arthrometry, pivot shift test and Lachman test (16)(17)(18)(19)(20)(21)(22)(23)(24), as well as reduced graft failure (22)(23)(24) and improved International Knee Documentation Committee (IKDC) objective score (18,23,24) compared with single-bundle ACL reconstruction. Therefore, double-bundle ACL reconstruction is indicated to be superior to single-bundle ACL reconstruction.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation